Pesticide Pressure on Insect and Human Population: A Review - , Monika Singh, Amit Kumar (Archives of Current Research International, 2024)
It is estimated that the current 7 billion world population would increase by 70 million people year, or 30%, to reach 9.2 billion by 2050. It is anticipated that this increased population density will result in a 70% rise in the demand for food production. This increase is mostly attributable to shifts in emerging countries' dietary trends toward higher-quality foods, such as increased consumption of meat and dairy products and the growing use of cereals for animal feed. There isn't much more agricultural land available. Any growth will primarily come at the price of forests and other natural ecosystems that support wildlife, wild cousins of crops, and organic pest adversaries. Additionally, rather than producing food, more agricultural land will be used to create bio-based commodities like fiber and biofuel. As a result, we must produce food on even less area, with even less water, and with less energy, pesticides, and fertilizer than we do now. There is an urgent need for sustainable production at elevated levels in light of these constraints. Reducing the present output losses resulting from pests is a significant obstacle to agricultural productivity. This review covers pest-related crop losses worldwide, estimates of productivity linked to pesticide use, costs and benefits of pesticide use, chemical yield loss reduction strategies, biological and recombinant pest control methods, and the difficulties facing the crop protection sector. In deciding how pesticides will be used in agriculture in the future, the general public plays a crucial role. However, the external issues related to the impacts of pesticides on human and environmental health must also be addressed as long as there is a need for pesticide-based solutions to pest management issues and food security concerns.